Pendidikan Anak dalam Keluarga di Era Digital - Andriyani, Isnanita Noviya (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Technological developments increasingly consistent in everyday life. Children grow along with the rapidly evolving technology, ranging from television to computers, smartphones, and digital tablet devices with various applications. The present generation of children, called